'Don't Read This on a Plane': a case study in microbudget feature filmmaking. Issue 2 (3rd May 2020) - McBratney, Stuart; Minichiello, Mario; Roxburgh, Mark
ABSTRACT: This paper presents demonstrable insights from the creation of a microbudget feature-length narrative drama film with high production values. As a case study, I am using a feature film I have written and directed titled "Don't Read This on a Plane", which was filmed in 10 countries, produced on a budget of A$125, 000 including all post-production, fees, and deliverables, and has been acquired for international distribution. I argue that by practicing pragmatism and bricolage, and by utilising a small professional crew who handle multiple roles, a microbudget filmmaker is able to transcend financial limitations. To support my argument, I detail my lived experience as a filmmaker from the project's conception in 2016 to its completion in 2020. In additional to describing my roles as the film's writer, co-financer, co-producer, director, editor, composer, and sound mixer, I also outline the involvement of key crew members. "Don't Read This on a Plane" embodies my tacit understanding of pragmatism and bricolage, and this paper shares my demonstrable approach to microbudget filmmaking.